2010
DOI: 10.1080/08276331.2010.10593480
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Internet and ICT Use among SME Agribusiness Growers and Producers

Abstract: Much of the small and medium-sized enterprise (SME) research examining adoption and use of Internet and information and communication technologies (ICT) has argued that firms adopt and use the Internetrelated ICTs to different extents depending on firm size, industry type and CEO education. To understand these issues most studies to date consider firms across industry sectors. The results though are mixed, implying the need to investigate industry-specific issues. While some SME ICT studies do target single in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Although these developments are improving the status quo, the systemic challenges in the EMDEs continue to inhibit the adoption and implementation of state-of-the-art technologies (Makiwa and Steyn 2018;Omotosho 2020;Suyambu, Anand, and Janakirani 2020;Wollschlaeger, Sauter, and Jasperneite 2017). The revolution in Internet technologies and telecommunications provide new and affordable ways for SMEs in these economies to market products and promote brands (Omotosho 2020;Burke 2010;Abdullah 2002). However, technology adoption by small businesses in EMDEs is years behind the counterparts in the advanced economies (Makiwa and Steyn 2018;MacGregor and Kartiwi 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although these developments are improving the status quo, the systemic challenges in the EMDEs continue to inhibit the adoption and implementation of state-of-the-art technologies (Makiwa and Steyn 2018;Omotosho 2020;Suyambu, Anand, and Janakirani 2020;Wollschlaeger, Sauter, and Jasperneite 2017). The revolution in Internet technologies and telecommunications provide new and affordable ways for SMEs in these economies to market products and promote brands (Omotosho 2020;Burke 2010;Abdullah 2002). However, technology adoption by small businesses in EMDEs is years behind the counterparts in the advanced economies (Makiwa and Steyn 2018;MacGregor and Kartiwi 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Van Dijk (2006) highlighted the effectiveness of ICT as a potent driver of economic development in South Korea as well as other South-East Asian nations. Also, Burke (2010) explained that ICT deployment (i.e ownership of websites) serves as a major boost to increased sales volume and new customers' acquisition drive by firms.…”
mentioning
confidence: 99%
“…Van Dijk (2006) indicated that ICT is being seen as an agent of economic development in South-East Asian countries especially in South Korea. Burke (2010) observed several important benefits from owning websites, such as having new customers and additional sales by firms.…”
Section: Introductionmentioning
confidence: 99%